Search for vectorlike charge 2/3 T quarks in proton-proton collisions at √(s) = 8 TeV - Khachatryan, V. (2016)
A search for fermionic top quark partners T of charge 2=3 is presented. The search is carried out in proton-proton collisions corresponding to an integrated luminosity of 19.7 fb-1 collected at a center-ofmass energy of √(s) = 8 TeV with the CMS detector at the LHC. The T quarks are assumed to be produced strongly in pairs and can decay into tH, tZ, and bW. The search is performed in five exclusive channels: a single-lepton channel, a multilepton channel, two all-hadronic channels optimized either for the bW or the tH decay, and one channel in which the Higgs boson decays into two photons. The results are found to be compatible with the standard model expectations in all the investigated final states. A statistical combination of these results is performed and lower limits on the T quark mass are set. Depending on the branching fractions, lower mass limits between 720 and 920 GeV at 95% confidence level are found. These are among the strongest limits on vectorlike T quarks obtained to date.